2017
DOI: 10.1007/s00059-017-4645-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma osteopontin levels in patients with dilated and hypertrophic cardiomyopathy

Abstract: Plasma OPN levels were associated with overall heart failure severity rather than with specific cardiomyopathy subtype in patients suffering from DCM or HCM, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…A study using coronary angiography showed that osteopontin levels were indeed associated with the presence and extent of coronary artery disease [ 38 ]. In line with our study, multiple studies also showed that elevated osteopontin may be a predictor of increased CVD risk in patients with diabetes [ 14 16 ], and osteopontin is elevated in heart failure patients [ 39 , 40 ]. Furthermore, osteopontin may also be involved in the coronary calcifications process by inhibiting hydroxyapatite formation [ 3 ].…”
Section: Discussionsupporting
confidence: 91%
“…A study using coronary angiography showed that osteopontin levels were indeed associated with the presence and extent of coronary artery disease [ 38 ]. In line with our study, multiple studies also showed that elevated osteopontin may be a predictor of increased CVD risk in patients with diabetes [ 14 16 ], and osteopontin is elevated in heart failure patients [ 39 , 40 ]. Furthermore, osteopontin may also be involved in the coronary calcifications process by inhibiting hydroxyapatite formation [ 3 ].…”
Section: Discussionsupporting
confidence: 91%
“…Cardiac hypertrophy is associated with increased expression of active NHE1 and OPN (10,43,44). However, a recent finding demonstrated that plasma OPN level is significantly increased in dilated cardiomyopathy subtype rather than hypertrophic cardiomyopathy, indicating that plasma OPN level is associated with overall heart failure severity (28). Our previous research had demonstrated that OPN is involved as a regulator in NHE1-induced cardiac hypertrophy in vitro (22,23).…”
Section: Discussionmentioning
confidence: 86%
“…OPN also appears to play a role in several cardiomyopathies, including diabetic cardiomyopathy, in vivo [44,45] DCM both in mice [46] and in humans [7] and in patients with HCM [26]. The implication of OPN in idiopathic cardiomyopathies was also observed in hearts explanted at the time of cardiac transplantation, revealing an upregulation of OPN in cardiomyocytes [47].…”
Section: Role Of Opn In Heart Diseasementioning
confidence: 90%
“…The diverse biological functions of OPN can be attributable due to its structural features, PTMs, interaction with multiple receptors, and different isoforms [5,17]. Alternative translation of OPN generates two isoforms: A cell-secreted full length OPN (sOPN) and a shortened protein lacking the N-terminal signal sequence of sOPN, intracellular (iOPN), found in the cytoplasm and nucleus [26]. Studies investigating the involvement of OPN in cardiovascular diseases primarily focus on total OPN expression and do not take into account the expression levels of any specific OPN isoform [21].…”
Section: Osteopontin Structurementioning
confidence: 99%
See 1 more Smart Citation